Use of cashew gum combined with galactomannan for encapsulation of Rosmarinus officinalis essential oil - Mendes, Luana Guabiraba; Mendes, Francisco Rogênio da Silva; Furtado, Roselayne Ferro; Freire, Gabrielle Albuquerque; Sales, Gleilton Weyne Passos; Costa, José Maria Correia da; Nogueira, Nádia Accioly Pinto; Monteiro-Moreira, Ana Cristina de Oliveira; Moreira, Renato de Azevedo (Journal of Environmental Analysis and Progress, 2020)
Encapsulating matrices are important to maintain the properties, promote the low and controlled release, and avoid these bioactive compounds' undesirable reactions. This study's objective was to evaluate cashew gum (CG) use combined with galactomannan (GAL) in the rosemary essential oil encapsulation by atomization. During the emulsification, the polysaccharides were crosslinked with sodium trimetaphosphate. The particles obtained after encapsulation were evaluated for moisture, solubility, particle size, encapsulation efficiency, morphology, antimicrobial activity, and chemical composition of the essential oil volatiles. GAL/CG blend showed higher encapsulation efficiency and lower oil release than the cashew gum matrix. Undoubtedly, galactomannan combined with cashew gum improved the microparticles' characteristics due to the galactomannan's high emulsifying property even in low concentration. Essential oil maintained its antimicrobial and chemical properties practically after the encapsulation procedure.